Pelatihan Patient Safety pada Himpunan Mahasiswa Anestesiologi ITS PKU Muhammadiyah Surakarta (HIMANES) - Suyanti Suyanti; Naufal Annasy (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
Patient safety is an important aspect in health services, especially in the field of anesthesiology. This training aims to improve the understanding and skills of members of the ITS PKU Muhammadiyah Surakarta Anesthesiology Student Association (HIMANES) in implementing patient safety principles. This community service uses a quantitative method with a pre-experimental one-group pre-test and post-test design. Respondents consisted of 20 HIMANES students. The results of the community service showed a significant increase in students' understanding and skills after being given training, as indicated by a significant difference in pre-test and post-test scores.